The Relationship between Work Discipline and TAS (School Administrative Personnel) Performance Results - Surya, Winanda; Sulastri, Sulastri; Triwiyanto, Teguh (Proceedings Series of Educational Studies, 2024)
Work discipline greatly affects the performance results of an organization. Schools as an organization have school administration personnel who serve all administrative matters in the school. The question in this article research is how much effect does work discipline have on the performance results of school administration personnel (TAS)?, To answer this question, the researcher uses the SLR method and collects literature (material materials) sourced from books, journals, and other sources. As a result, work discipline has a great influence on the performance results of school administration personnel (TAS). A school administration staff (TAS) who has high work discipline has a very important role, indirectly will have a positive effect on school operations and support the smooth operation of the school.